ANALISIS PROKSIMAT, AKTIVITAS ANTIOKSIDAN, DAN KOMPOSISI PIGMEN Ulva lactuca L. DARI PERAIRAN PANTAI KUKUP - da Costa, Junet Franzisca; Merdekawati, Windu; Otu, Ferly Rambu (Widya Mandala Surabaya Catholic University, 2018)
Seaweed has been widely consumed in Asia include Indonesia, especially coastal community. Seaweed has nutrients and non-nutrients compound that benefit health. Unfortunatelly, information about the potential of edible seaweed is limited. The objective of this study is to analyze the total nutrient levels (proximate), antioxidant activity, and pigment composition of Ulva lactuca L. that grow abundantly in Pantai Kukup, Gunung Kidul regency, Central Java. Ulva lactuca L. had 11.53% of water content, 2.94% of ash content, 5.17% of fat, 17.43% of protein, and 62.93% of carbohydrate. Antioxidant test by using DPPH found that inhibition concentration (IC50) of Ulva lactuca L. was 88890.55 ppm. Ulva lactuca L. contain chlorophyll a, b, and c, neoxanthin, anteraxanthin, dinoxanthin, flavoxanthin, micronone, and vaucheriaxanthin and other unidentified pigments. Ulva lactuca L. has high carbohydrate and protein with low lipid, which is potential as functional food material. Moreover, Ulva lactuca L. showed antioxidant activity, which is prospective in health, pharmaceutical, cosmetic.